2018
DOI: 10.1016/j.jbusres.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Big data, big decisions: The impact of big data on board level decision-making

Abstract: The paper explores whether 'Big Data' (BD) has changed the process of board-level strategic decision-making. To enable a rich understanding of the issues, we gained access to directors of UK-based global organizations who were routinely involved in high-level strategic decision-making, undertaking lengthy semi-structured interviews.The quality of the data achieved is therefore a distinctive feature of our study. Our data reveal important findings in three broad areas. First, we explore the cognitive capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(118 citation statements)
references
References 91 publications
2
94
0
1
Order By: Relevance
“…Digitally supported marketing allows an initiative to move from an idea or concept to execution in weeks or even days, compared to the months or years suggested in classic marketing (Chaffey and Ellis-Chadwick, 2019). More generally, the impact of big data on board decisions has been researched by Merendino et al (2018). The impact of the digitisation of data on board decisions has been explored by Dibb et al (2015).…”
Section: Planning Processesmentioning
confidence: 99%
“…Digitally supported marketing allows an initiative to move from an idea or concept to execution in weeks or even days, compared to the months or years suggested in classic marketing (Chaffey and Ellis-Chadwick, 2019). More generally, the impact of big data on board decisions has been researched by Merendino et al (2018). The impact of the digitisation of data on board decisions has been explored by Dibb et al (2015).…”
Section: Planning Processesmentioning
confidence: 99%
“…Other authors emphasize the importance of human aspects, like analytical skills or managers' abilities (e.g. Akhtar, Frynas, Mellahi, & Ullah, 2019;Merendino et al, 2018). On the other hand, some scholars focus more on organizational aspects like for example organizational agility (e.g.…”
Section: The Relationship Of Big Data and Organizational Performance mentioning
confidence: 99%
“…However, to generate value from CRM Analytics, they argue that "it needs to be transformed into a dynamic capability" (Sena et al, 2019, p. 224). In semi-structured interviews, Merendino et al (2018) explored if big data has an influence on board level decision making. They found that there are limited capabilities for dealing with big data at that level and suggest that boards need to develop valuable big data capabilities.…”
Section: The Human Dimensionmentioning
confidence: 99%
“…Prior studies have emphasised the increasingly important component of BDA in organisational decision-making processes (Merendino et al, 2018;Hagel, 2015). Given that BDA is considered as "a major differentiator between high-performing and low-performing organizations" (Liu, 2014, p. 40-42), it can be argued that BDA can ultimately be utilised or to help explain why some organisations fail and others survive and enjoy continuous success in this era of big data.…”
Section: Big Data Analyticsmentioning
confidence: 99%